Hubungan Kegemukan dengan Prestasi Akademik pada Remaja: Literature Review - Paramudhita, Fiska Azzahra (Universitas Airlangga, 2024)
Background: Adolescents at the age of growth need greater nutritional intake because the imbalance between nutrient intake and the recommended nutritional adequacy has been one of the causes of nutritional problems that occur in adolescents. Obesity, chronic lack of energy, and anemia were the most common nutritional problems in adolescents in Indonesia. Academic achievement was the main indicator to determine the ability of students, as well as being one of the determinants of the quality and main goals of education. There were a number of factors that affect academic achievement in adolescents, namely physical health, psychological (healthy, motivational, psychoemotional stability, school environment, and family classes. One element that had an important role in influencing the quality of human resources, namely health and nutrition. Thus, nutrition and nutritional status that were fulfilled produced quality human resources. Objectives: The literature review aims to analyze the relationship between obesity and academic achievement in adolescents. Methods: This research was conducted by literature review design obtained from national and international journal articles with content according to the topics discussed, in the form of original articles, full texts, open access, and published in the last 10 years, as well as the process of searching journal articles through Google Scholar, Science Direct, Elsevier and PubMed. Results: Based on 10 journal articles found, most journal articles state that there was a correlation between obesity and academic achievement in adolescents. Adolescents with good nutritional status would receive material and thought well, and obtain good academic performance as well because intelligence and ability to capture material could be influenced by a person's nutritional status. However, several other factors affect academic achievement in adolescents, in addition to nutritional status. Conclusions: Based on the analysis conducted, it was concluded that there was a relationship between obesity and academic achievement in adolescents. In addition, obesity was one of the factors influencing academic achievement.